Enabling Optical Steganography, Data Storage, and Encryption with Plasmonic Colors. Issue 3 (27th January 2021) - Song, Maowen; Wang, Di; Kudyshev, Zhaxylyk A.; Xuan, Yi; Wang, Zhuoxian; Boltasseva, Alexandra; Shalaev, Vladimir M.; Kildishev, Alexander V.
Abstract: Plasmonic color generation utilizing ultrathin metasurfaces as well as metallic nanoparticles holds a great promise for a wide range of applications including color displays, data storage, and information encryption due to its high spatial resolution and mechanical/chemical stability. Most of the recently demonstrated systems generate static colors; however, more advanced applications such as data storage require fast and flexible means to tune the plasmonic colors, while keeping them vibrant and stable. Here, a surface‐relief aluminum metasurface that reflects polarization‐tunable plasmonic colors is designed and experimentally demonstrated. Excitation of localized surface plasmons encodes discrete combinations of the incident and reflected polarized light into diverse colors. A single storage unit, namely a nanopixel, stores multiple‐bit information in the orientation of its constituent nanoantennae, which is conveniently retrived by inspecting the reflected color sequence with two linear polarizers. Owing to the broad color variability and high spatial resolution of the metasurface, the proposed encoding approach holds a strong promise for rapid parallel readout and encryption of high‐density optical data. The method also enables robust generation of dynamic kaleidoscopic images without the "cross‐talk" effect. The approach opens up a new route for advanced dynamic steganography, high‐density parallel‐access optical data storage, and optical information encryption. Abstract : The proposed anisotropic metasurface has significant potential for high‐density optical data storage, dynamic color image display, and encryption. With the experimentally validated approach, diverse colors from individual plasmonic nanopixels are decoded. These colors, which depend on nanopixel anisotropy and the incident and reflected polarizations, can be obtained with a new integrated parallel readout scheme capable of reaching ultrafast speeds.